Prevalence of Malnutrition among People Living with Obesity and Hypertension in African Region - Peter , Malachy Babangida; Wei , Calvin Ronchen; Peters , Esegbue; Ofili , Charles; Nwose , Ezekiel Uba (Current Innovations in Disease and Health Research Vol. 8, 2023)
The purpose of this review is to investigate the prevalence and relationship between malnutrition, metabolic syndrome, obesity and hypertension and to provide more evidence justifying the management of cardio-metabolic problems in obese hypertensive individuals. The prevalence of malnutrition among people living with obesity and hypertension signifies the coexistence of cardio-metabolic problems with 0besity and hypertension. Obesity can lead to a form of malnutrition characterized by excess body fat and excess or inadequate micronutrient intake. This nutritional paradox can exacerbate hypertension and increase the risk of cardiovascular disease. Factors contributing to this issue include poor dietary choices, limited access to nutritious foods, metabolic factors, and medications. Addressing malnutrition in obese hypertensive individuals is crucial for promoting their health and reducing complications, emphasizing the need for adequate diet, physical activity, and weight management. Obesity is a growing public health problem and should be kept in mind when treating patients with hypertension because it is a strong predictor of uncontrolled hypertension. As obesity and its metabolic and vascular effects remained during the years, research has provided evidence justifying the management of metabolic components in obese individuals. Obesity is a multi factorial pathology and chronic diet related non-communicable disease. The most widely used parameter for its diagnosis is the body mass index (BMI) which is not suitable for assessing the body fat and other metabolic components. Obesity specifically abdominal obesity is an independent risk factor for hypertension. Anthropometrics like the waist circumference, waist to height ratio (WHtR), waist-hip ratio (WHR) and metabolic/biochemical components should be considered in the diagnosis of obesity.